A Structured Workshop to Improve Chart Documentation Among Housestaff - Jaideep Talwalkar; Jason Ouellette (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a series of workshops designed to assist internal medicine residents in developing chart documentation skills. In a series of hour-long workshops, notes written by house staff in both the inpatient and outpatient settings are used as a springboard for discussion. Together with faculty, house staff critique the notes and score them using instruments developed for this purpose. Methods This resource was designed specifically for use with international medical graduates, who often face communication barriers with patients, staff, and faculty due to differences in language and culture, but can be used with any group of internal medicine trainees. Program materials can be modified to suit the needs of educators in other fields of medicine. This resource addresses the Accreditation Council for Graduate Medical Education requirement that internal medicine residency programs review "clinical documentation for format, quality of data entry, accuracy of the assessment, and appropriateness of the plan." Results In a preimplementation needs assessment, house staff revealed that they value feedback related to chart documentation and would like more formal education in this area. Faculty members also placed value on the teaching of note-writing skills, and were particularly interested in improving the quality of hospital discharge summaries. In extemporaneous commentary, house staff have stated that they consider points learned from this resource on a regular basis during their daily work. House staff have also reported that they have a better understanding of the expected format and content of various notes. A formal postimplementation program evaluation is in progress and will include analysis of house staff self-reported confidence and satisfaction as well as a chart review to measure actual change in quality of notes. Discussion Internal medicine training programs may improve the quality of house staff chart documentation by implementation of this structured series of interactive workshops. House staff value feedback related to their own chart documentation skills, but may be hesitant to publicly provide this feedback to their peers.